A new genus of Protosmylinae from the Middle Jurassic of China (Neuroptera: Osmylidae) - Wang, Yongjie; Liu, Zhiqi; Ren, Dong; Shih, Chungkun (Zootaxa, 2010)
Three new fossil lacewings, Juraheterosmylus antiquates gen. et sp. nov., Juraheterosmylus astictus sp. nov. and Juraheterosmylus minor sp. nov. are described from the Middle Jurassic of Daohugou, Inner Mongolia, China. The new genus, assigned to Protosmylinae, is the oldest record of the subfamily. A diagnosis of Protosmylinae is provided and biogeographical distribution of Protosmylinae is discussed.